Geophysical and hydrogeological characterization of the sub-basins of Apan and Tochac (Mexico basin) - A. Huidobro-González; O. Delgado-Rodríguez; J. Lermo-Samaniego; J. O. Campos-Enríquez; Huizar-Alvarez, R. (Geofísica Internacional, 1997)
The main features of the hydrogeologic system in the Apan and Tochac sub-basins of the basin of Mexico are described from gravity, magnetic, resistivity, hydrogeological, and geochemical data. Both sub-basins have about 600 m of vol¬cano-sedimentary infill, and are separated by the NE-SW trending Apan range. Gravity and magnetic data indicate that the Apan range is emplaced along a major NE-SW trending fault along the extension of a regional lineament joining the Tlaloc and Telapon volcanoes. The Apan sub-basin has low-level seismic activity. A correlation with borehole data confirms a model of the hydrogeologic system which includes intergranular, mixed and fissured aquifers with transmissivities between 5.7 x 10-3 m2/sec and 1.1 x 10-1 m2/sec, and permeability around 4.0 x 10-4. The fissured aquifer is the recharge area, while the other two aquifers constitute a semi-confined aquifer whose only discharge comes from well pumping. The unsaturated zone is 60 m thick and the potentiometric surface fluctuates 0.30 m yearly. However, in places no fluctuations were ob¬served. The thickest portion of the aquifer, as delimited by vertical electric soundings and boreholes, is in the southern por¬tion of the Tochac sub-basin. Resistivity values and hydrogeochemical studies indicate the presence at depth of good qual¬ity, slightly mineralized water.